Enhancement of Liver and Kidney Ultrasound Images by Using Digital Image Processing Techniques - Othman, Faizah (Universiti Teknologi Petronas, 2004)
Liver and kidney are two important organs in human body. Both ofthem play a vital role in regulating life processes, especially in digestion and excretion system. However, both liver and kidney diseases persist as a very common disease across the nation. Annually, thousands of patients suffer from both diseases. In Malaysia itself, the statistics shows that average of 1,000 people die due to kidney problem in a year [15]. Today, with the rapid movement of technology, unnecessary measures like surgery can be avoided. Doctors and health practitioners can simply diagnose the mass or tumor by using Medical Imaging Techniques such as Computer Tomography (CT scan), Magnetic Resonance Imaging (MRI), Ultrasound Imaging and X-Ray. The project involves on detecting liver and kidney diseases by using Ultrasound Imaging method. These days, doctors and radiologists have a difficulty in diagnosing raw ultrasound images of any internal organs that consist of soft tissue (i.e.: liver and kidney). Those unprocessed images cannot give patent image to doctors and radiologists in order for them to acquire essential information such as shape, texture andcomposition of tumors andcysts. The gist of the project is to enhance the images of both organs for a better outlook so that doctor can easily diagnose it. The principle of Digital Image Processing (DIP) and its application for liver and kidney ultrasound images has been selected as a field of research for this final year project. The objective of this project is to develop a technique in enhancing the imaging investigation of liver and kidney patients by using Ultrasound Imaging method. This method is safe, cheaper, faster and radiation free. A Digital Image Processing (DIP) fundamental was employed in achieving better quality of images. Literature review of both liver and kidney diseases was reviewed first before the images were processed. Besides, knowledge of Image Processing was mastered before the images were enhanced. Samples of 15 kidney images and 10 liver images from various type of disease were processed by using Matlab 6.1 software. Theresult was found satisfy since the quality of the new images was clearer compare to the raw images. Nevertheless, future work will continue by applying Neural Network system in order to get pattern recognition for the process image.